The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/iub.1643
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic interaction of aminophylline–riboflavin leads to ROS‐mediated DNA damage and cell death: A novel phototherapeutic mechanism for cancer

Abstract: The accompanied tissue devastation and systemic toxicity of chemotherapy has shifted the quest for having an effective and palliative cancer therapy towards photodynamic therapy (PDT). Riboflavin (Rf), an essential micronutrient is emerging as a potent tool of PDT, due to its excellent photosensitizing properties. It can be used as an efficient adjuvant for various anticancer drugs. The hemolytic and proteolytic effect of photoilluminated aminophylline (Am), a xanthine derivative, and Rf is well documented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
2
6
0
Order By: Relevance
“…3a) showed significant intracellular ROS generation. Our results are supported by studies from our lab [[33], [34], [35]] and those of others [36,37] that photoactivated riboflavin does produce ROS. Riboflavin absorbs photons from the illuminated light and undergoes intersystem conversion i.e.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3a) showed significant intracellular ROS generation. Our results are supported by studies from our lab [[33], [34], [35]] and those of others [36,37] that photoactivated riboflavin does produce ROS. Riboflavin absorbs photons from the illuminated light and undergoes intersystem conversion i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Our results can be correlated with previous findings of antibiotic lethality due to altered redox status [40]. The effect of ROS scavengers on oxidative damage induced by photoilluminated riboflavin generated oxygen radicals has already been explored previously in our lab [34,41] and it has been clearly observed that if any protein/compound/enzyme is added that can quench generated ROS, then the detrimental effect of ROS is inhibited. Therefore, if any ROS quencher will be present in solution the bacterial inactivation will be hindered.…”
Section: Discussionsupporting
confidence: 89%
“…Esophageal cancer has high morbidity and mortality, partly because patients tend to be diagnosed at an advanced stage and with esophageal obstruction, which seriously affects their quality of life. Thankfully, an effective medical treatment, PDT, has been found to relieve the esophageal obstruction by inducing localized tumor destruction via the photochemical generation of cytotoxic singlet oxygen [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…However, the HUVEC cells seemed to recover over the next 24 h, and cytotoxicity was only observed 72 h post exposure at 200 µg/mL with the 7 J/cm 2 light dose (Table 1). In the presence of 7 J/cm 2 light dose, which represented the minimal light dose the vessel would be exposed to during in vivo treatment [9,18,19], cytotoxic effects were only observed with the highest concentration of the 10-8-10 Dimer (200 µg/mL) at 24, 48 and 72 h post exposure. The dose of 200 µg/mL is about 1000-fold above the dose of 10-8-10 Dimer which is delivered to the vascular tissues during in vivo or in vitro dosing with a 2 mg/mL 10-8-10 Dimer solution [17].…”
Section: Cell Viability Following Photochemical Treatmentmentioning
confidence: 99%